2015
DOI: 10.1007/s13361-015-1094-1
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Electron Capture Dissociation Mass Spectrometry of Phosphopeptides with Traveling Wave Ion Mobility Spectrometry and Molecular Dynamics Simulations

Abstract: Electron capture dissociation mass spectrometry offers several advantages for the analysis of peptides, most notably that backbone c and z fragments typically retain labile modifications such as phosphorylation. We have shown previously that, in some cases, the presence of phosphorylation has a deleterious effect on peptide sequence coverage, and hypothesized that intramolecular interactions involving the phosphate group were preventing separation of backbone fragments. In the present work, we seek to rational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…This would explain why in some cases we observed a decrease in cross section for phosphopeptides compared with their less massive, unmodified analogues. This is in agreement with previous studies that suggest phosphorylated residues participate in intramolecular interactions in peptide ions [29, 30, 39]. …”
Section: Resultssupporting
confidence: 94%
“…This would explain why in some cases we observed a decrease in cross section for phosphopeptides compared with their less massive, unmodified analogues. This is in agreement with previous studies that suggest phosphorylated residues participate in intramolecular interactions in peptide ions [29, 30, 39]. …”
Section: Resultssupporting
confidence: 94%
“…In both cases, increased conformational heterogeneity and reduced stabilization of higher order (secondary) structure by hydrogen bonding were posited to account for the increased fragmentation observed in ions that possessed more internal energy. Cooper and coworkers recently expanded this type of work beyond the analysis of secondary structure only, and used a combination of ECD, ion mobility, and molecular dynamics simulations to investigate the nature of intramolecular interactions within six related pentadecapeptides . Due to the presence of tertiary and quaternary structure in native proteins and complexes, their behavior in ExD experiments is, of course, even more complex than that of peptides, and will be discussed in a later section.…”
Section: Determinants Of Exd Fragmentation Behavior Of Peptidesmentioning
confidence: 99%
“…Cooper and coworkers recently expanded this type of work beyond the analysis of secondary structure only, and used a combination of ECD, ion mobility, and molecular dynamics simulations to investigate the nature of intramolecular interactions within six related pentadecapeptides. 161 Due to the presence of tertiary and quaternary structure in native proteins and complexes, their behavior in ExD experiments is, of course, even more complex than that of peptides, and will be discussed in a later section. In the next section, we will briefly consider a different area where ECD and ETD have played a significant role, namely the analysis of post-translational modifications.…”
Section: Effect Of Higher Order (Secondary) Structurementioning
confidence: 99%
“…Phosphorylated residues are thought to be involved in multiple intramolecular interactions of peptide ions, and previous work 30,43 on several doubly charged phosphopeptide ions has suggested that intramolecular salt bridges or ionic hydrogen bonds are formed between phosphate and basic groups in specific sequences.…”
Section: Resultsmentioning
confidence: 99%
“…However, this model does not currently take into account sequence-specific features, such as positional information or residue combinations. Also, in this model, changes in CCS upon phosphorylation are treated as increases in CCS 24,29 , and it is not possible to explain the decrease in CCS due to phosphorylation that is seen in certain sequences 24,30 . Furthermore, the model was developed using doubly charged peptides with molecular weights ranging from 1,000 Da to 1,400 Da, and thus cannot be applied directly to larger, more highly charged ions in the 600 Da to 5,000 Da range that are commonly found in proteomics experiments.…”
Section: Introductionmentioning
confidence: 99%